Effects of carbon nanofiber on physiology of Drosophila - Lee SH (Dove Medical Press, 2015)
Shin-Hae Lee,1,* Hye-Yeon Lee,1,* Eun-Ji Lee,1,* Dongwoo Khang,2 Kyung-Jin Min11Department of Biological Sciences, Inha University, Incheon, Republic of Korea; 2Department of Molecular Medicine, Graduate School of Medicine, Gachon University, Incheon, Republic of Korea*These authors contributed equally to this workAbstract: As nanomaterials are now widely utilized in a wide range of fields for both medical and industrial applications, concerns over their potential toxicity to human health and the environment have increased. To evaluate the toxicity of long-term exposure to carbon nanofibers (CNFs) in an in vivo system, we selected Drosophila melanogaster as a model organism. Oral administration of CNFs at a concentration of 1,000 µg/mL had adverse effects on fly physiology. Long-term administration of a high dose of CNFs (1,000 µg/mL) reduced larval viability based on the pupa:egg ratio, adult fly lifespan, reproductive activity, climbing activity, and survival rate in response to starvation stress. However, CNFs at a low concentration (100 µg/mL) did not show any significant deleterious effect on developmental rate or fecundity. Furthermore, long-term administration of a low dose of CNFs (100 µg/mL) increased lifespan and climbing ability, coincident with mild reactive oxygen species generation and stimulation of the antioxidant system. Taken together, our data suggest that a high dose of CNFs has obvious physiological toxicity, whereas low-dose chronic exposure to CNFs can actually have beneficial effects via stimulation of the antioxidant defense system.Keywords: toxicity, Drosophila melanogaster, lifespan, reactive oxygen species